2020
DOI: 10.1093/biolre/ioaa178
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of ADM and ADM2 by hypoxia regulates migration of trophoblast and HLA-G expression†

Abstract: Preeclampsia (PE) is a placental disorder caused by endothelial dysfunction via trophoblast inadequate invasion activity. Adrenomedullin (ADM) and ADM2 are multi-functional peptides that can support vascular activity and placental growth. However, correlation between ADMs and trophoblast functions is currently unclear. The objective of this study was to analyze changes in expression of ADMs in placenta and HTR-8/SVneo trophoblast cells under hypoxia and their effects on invasion activity of trophoblast cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Moreover, it is used as a target for diagnosis in clinical trials 33 . ADM is involved in immune regulation and trophoblast invasion under hypoxic conditions 34 . ARRB1 has been demonstrated to be a potential tumor promoter in prostate cancer and is important for metabolic alterations in prostate cancer 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is used as a target for diagnosis in clinical trials 33 . ADM is involved in immune regulation and trophoblast invasion under hypoxic conditions 34 . ARRB1 has been demonstrated to be a potential tumor promoter in prostate cancer and is important for metabolic alterations in prostate cancer 35 .…”
Section: Discussionmentioning
confidence: 99%
“…In 1997, HLA-G was first proved to have a protective effect on the fetus after semi-allogeneic transplantation in the maternal immune system, which was also supported in pathological research by Yie et al ( 23 ). Nowadays, HLA-G is considered to be a major immune checkpoint molecule and plays a crucial role in maternal-fetal immune tolerance ( 24 , 25 ). HLA-G can increase the activation threshold of immune cells before immune response by up-regulating the expression of inhibitory receptors on immune cells such as dNK cells and decidual T cells ( 26 28 ).…”
Section: Immunomodulatory Effect Of Hla-gmentioning
confidence: 99%
“…And some research showed that low O 2 levels can also promote EVT invasion. [8,[10][11][12][13] Therefore, a physiological hypoxic environment exists at the maternal-fetal interface during early pregnancy. However, there is a pathological hypoxic microenvironment in patients with PE, and the underlying pathological mechanisms remain unknown.…”
Section: Introductionmentioning
confidence: 99%